2007
DOI: 10.3727/154427207783948757
|View full text |Cite
|
Sign up to set email alerts
|

Put Me in the Zoo! A Laddering Study of Zoo Visitor Motives

Abstract: Understanding why people visit zoos and other nature-oriented attractions is critically important for developing exhibits and programming, as well as promoting the attraction to potential visitor markets. Means-end theory and its associated methodology known as laddering provide a useful framework for characterizing the relationships between the attributes of a choice option (such as a visitor attraction), the consequences (i.e., the benefits or costs/risks) associated with those attributes, and the personal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…Previous zoo studies showed that satisfaction with these attributes is associated with visitors' perceptions (Finlay et al, 1988;Klenosky & Saunders, 2008;Reade & Waran, 1996): viewing time (Johnston, 1998) and visitors' learning (Pearson et al, 2013). For example, Klenosky and Saunders (2008) urged that "animals in natural exhibits were perceived by visitors as being more active and happier, which lead to visitors feeling happier and enjoying their visit, and being more likely to trust the zoo and support conservation efforts" (p. 325). Reade and Waran (1996) also concluded that removing adverse effects on animal welfare by providing aesthetically pleasing enclosures is vital in fostering a positive perception of zoos and their animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous zoo studies showed that satisfaction with these attributes is associated with visitors' perceptions (Finlay et al, 1988;Klenosky & Saunders, 2008;Reade & Waran, 1996): viewing time (Johnston, 1998) and visitors' learning (Pearson et al, 2013). For example, Klenosky and Saunders (2008) urged that "animals in natural exhibits were perceived by visitors as being more active and happier, which lead to visitors feeling happier and enjoying their visit, and being more likely to trust the zoo and support conservation efforts" (p. 325). Reade and Waran (1996) also concluded that removing adverse effects on animal welfare by providing aesthetically pleasing enclosures is vital in fostering a positive perception of zoos and their animals.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various research methodologies have been used to explore the satisfaction of zoo visitors. For example, Klenosky and Saunders (2008) introduced the laddering technique as a method of understanding the factors that influence people's decisions to visit a zoological park. Q methodology, a method specifically intended to capture people's subjectivity, was used by Sickler and Fraser (2009), who focused on the construct of enjoyment rather than satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Since the four objectives have been persuasively critiqued by Jamieson (2006) and others, we ought not to resolve the tensions in favor of these objectives over the display practices. Almost no one supports the idea that animal captivity is justified by the objective of human recreation (although, interestingly, the research into what zoo-goers actually achieve during a zoo visit is just that [Turley 2001;Klenosky and Saunders 2008]); the empirical claim that zoos provide meaningful educational experiences or conduct important scientific research has been shown to be highly questionable-zoo-goers tend to ignore the educational displays about the animals, and any science would necessarily study the animal's responses to captivity, rather than the animal's 'natural' behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Internationally one of the predictors of visitation to an educational leisure setting is whether the individual visited the facility as a child Klenosky & Saunders, 2008). This is a problem in South Africa where many African and to a lesser extent Indian people are unlikely to have had the opportunity to visit an aquarium or a zoo 20 years ago.…”
Section: Catering For Different Life Experiencesmentioning
confidence: 99%